Влияние параметров исполнительного механизма на показатели работы линейного двигателя в системе привода наклона вагонов скоростных поездов - Омельяненко, В.И.; Любарский, Б.Г.; Якунин, Д.И. (Електротехніка і електромеханіка, 2011)
By the example of solving a test problem with a mathematical simulation model, an algorithm of a linear motor parameters choice for a body tilt system drive is introduced; a problem of actuating mechanism and linear motor parameters choice is formulated as a multicriterion optimization problem.